SELOKO ADAT ULUR ANTAR SERAH TERIMA ADAT PADA PERNIKAHAN ADAT MELAYU JAMBI: KAJIAN BENTUK DAN FUNGSI - Maizar Karim (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
The purpose of this study is to describe the form and function of Jambi Malay customs seloko. Seloko adat here is a custom seloko contained in the procession of customary stir between custom handover at the traditional marriage of Jambi Malay. The method used in this research is descriptive-qualitative. The data of this research are word unit, phrase, clause, sentence, text of the ceremony of repetition between the handover of customary marriage of Fortuna Mazka and the text of seloko in the Customary Principles of Sepucuk Jambi Sembilan Lurah (2001). The two texts are reconstructed philologically (critical edition) as the study material.The results of this study indicate that seloko adat ulur between handover of Jambi Malay custom has five forms: (1) kato adat or kato undang (2) kias word (3) kato penyelo (4) petatah-petitih and (5) pantun. Each form has a typology of rhyme, array, stanza, and conventional formulas. Seloko adat ular between the hand-over of Jambi Malay customary has various functions: (1) informational, (2) expressive, (3) directive, (4) aesthetic, and (5) fatik. These functions are firmly attached to each form of the shell, with Jambi's diction and local ideology.